SUBMICROSCOPIC CОNDITION OF HEMOCAPILLARIES OF HEART IN EXPERIMENTAL THERMAL TRAUMA AND LYOPHILIZED XENOGRAFTS USING - Viter, V.S.; Volkov, K.S.; Nebesna, Z.M. (World of Medicine and Biology, 2013)
In the experiment on white rats electronicmicroscopic changes of blood capillaries of myocardium were researched in severe thermal trauma and lyophilized xenografts usage. It is proved that xenografts using prevents development of destructive changes in the hemocapillaries of the heart in early terms of experiment and causes positive effects on regenerative processes and normalization of microcirculatory bed in late stages of experiment.